Wojciech Jaruzelski, Starsi o 30 lat, Wydawnictwo Adam Marszałek, Toruń 2011, ss. 205. - KOSMAN, Marceli (Przegląd Politologiczny, 2018)
Wojciech Jaruzelski, Starsi o 30 lat, Wydawnictwo Adam Marszałek, Toruń 2011, ss. 205.